Risk evaluation of uncertainties in generation scheduling using Monte Carlo simulation - Usman, M. D. M. (IEEE, 2012)
The sheer physical size of integrated power systems, containing various generation technologies in a competitive market environment, could procreate uncertainties in system operation that challenge the capability to serve committed load demand to the full extent. In this paper, risk assessment of the uncertainties associated with system generation in the operation planning horizon is investigated. Probability models describing uncertainties in system generation and projected load demand are constructed. Using Monte Carlo Simulation (MCS), Loss of Load probability (LOLP) is calculated for a six-bus case study. The LOLP is further used to quantify the exact amount of lost load due to contemplated uncertainties. The proposed approach can be useful to operators to make decisions concerning uncertainties arising in the generation side of the system.